With a vengeance : a novel [large type] - Sager, Riley (Thorndike Press large print basic, 2025)
"In 1942, six people destroyed Anna Matheson's family. Twelve years later, she's ready for retribution. Under false pretenses, Anna has lured those responsible for her family's downfall onto a luxury train from Philadelphia to Chicago, an overnight journey of thirteen hours. Her goal? Confront the people who've wronged her, get them to confess their crimes, and deliver them into the hands of authorities waiting at the end of the line. Justice will at last be served. But Anna's plan is quickly derailed by the murder of one of the passengers"--